Public Service Quality in Buahbatu District Bandung City - khoerunisa, angelina; Heri (Social Impact Journal, 2025)
Basically, as a public servant, the government must be responsible and capable of providing the best for the community in order to maintain public trust in the government. As a public service provider, the government is obliged to provide good public services to fulfill the rights of citizens. This study analyzes the Quality of Public Services in Buahbatu District, Bandung City, based on Bandung Mayor Regulation Number 64 of 2019 concerning Guidelines for the Implementation of Service Standards. The research method uses a qualitative approach with data collection through interviews, field observations, and document studies. This study identifies service quality, influencing factors, and efforts to overcome obstacles, using a service quality theory that includes efficiency, responsiveness, and non-partisanship. The results indicate that Buahbatu Subdistrict has improved efficiency through service standards and an official website, with varying service times. Responsiveness is good, with uncomplicated procedures and friendly service, although there are complaints about requirements. Services are provided fairly, but procedures for reporting unfairness are not yet fully known to the public. Influencing factors include access to technology and socialization of suggestion facilities. Efforts to address service quality barriers in Buahbatu Subdistrict, Bandung City, include improving transparency and accessibility of information by providing more detailed and easily understandable guidelines, and Buahbatu Subdistrict can implement an online queuing system that allows residents to obtain a queue number via the website before visiting the Subdistrict Office.